Mandatory CSR expenditure and firm performance. Issue 3 (December 2019) - Bhattacharyya, Asit; Rahman, Md Lutfur
Abstract: India has recently mandated corporate social responsibility (CSR) expenditure under section 135 of the Indian Companies Act 2013 – the first national jurisdiction to do so. In line with the "shareholder value maximization" concept, we document the positive impacts of CSR expenditure on firm performance measured by return on asset and cash flow from operations. Additionally, we find that, despite the regulatory requirement, mandated CSR legislation is a significant but not the sole determinant of actual CSR spending by firms; rather, firm-specific economic factors such as size, level of cash balance and cash flow from operations have a moderating effect. We also observe that CSR expenditure contributes to firm performance irrespective of the level of actual CSR expenditure relative to the level of mandatory CSR expenditure. Our findings potentially reconcile conflicting results presented in the literature and provide valuable information for governments and regulatory authorities that are considering the mandatory implementation of CSR expenditure.